2019
DOI: 10.1002/cssc.201802851
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Hydrocarbon Oligomer Solvent Systems for Sequestration of Trace Organics from Water

Abstract: Low‐viscosity poly(α‐olefin)s (PAOs) either alone or with functional hydrocarbon oligomer cosolvents are nontoxic, nonvolatile, recyclable solvent systems that effectively and efficiently sequester trace amounts of nonpolar organic compounds such as benzene and halogenated organics from water. More polar compounds including perfluorooctanoic acid and nitrobenzene or water‐miscible compounds such as THF and triethylamine can also be sequestered if the PAO phase contains an H‐bonding PAO‐anchored cosolvent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…1 These attributes make them useful in simple recycling schemes that involve liquid−liquid extractions with polar solvents. 2 Their low flammability makes them safer as a solvent for pyrophoric chemicals. 3,5,6 They also have applications in cosmetics since they are as nontoxic as mineral oil.…”
Section: ■ Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…1 These attributes make them useful in simple recycling schemes that involve liquid−liquid extractions with polar solvents. 2 Their low flammability makes them safer as a solvent for pyrophoric chemicals. 3,5,6 They also have applications in cosmetics since they are as nontoxic as mineral oil.…”
Section: ■ Introductionmentioning
confidence: 99%
“…3,5 These favorable properties, coupled with their separability, have led us to examine the use of PAOs as solvents in various chemical transformations. 2 Prior work by the Bergbreiter group demonstrated that PAO solutions can be used to recycle hydrocarbon-soluble catalysts or to sequester organic small molecules from polar solutions. For example, in a PAO medium, polyisobutylene (PIB) bound sulfonic acids were useful as esterification catalysts, 7 and the ester products could be isolated by vacuum distillation, quantitatively recycling the catalyst and the PAO solvent.…”
Section: ■ Introductionmentioning
confidence: 99%
See 3 more Smart Citations